1535. Expedición en busca del Rey Blanco - 1535. Expedition in search of the white king - Santos López, Pascual (Andelma, 2007)
It recounts the expedition of Don Pedro de Mendoza in 1534 and the founding of the city of Buenos Aires through the vision of the book of Ulrich Schmidl, with news of his men, among whom was the ciezano Juan de Aroca. There is also talk of the founding of Asunción and the survivors of the expedition.